2019
DOI: 10.1111/jppi.12281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Governance Climate Within Disability Service Organizations from the Perspective of Allied Health Professionals

Abstract: Within the healthcare service sector across many Western countries, clinical governance frameworks have been adopted to ensure consistent and effective service provision. There is merit in adopting such frameworks within disability service organizations as a mechanism to enhance service quality. This study explored whether disability service organizations exhibit organizational climates conducive to supporting clinical governance from the perspective of allied health professionals (AHPs). A total of 88 AHPs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Aspects of good health governance encompass oversight, policy guidance, collaboration, regulation, accountability and system design and require a human rights approach, technical and political action, and attention to corruption ( 20 ). Clinical governance is defined by healthcare providers' accountability for continuously improving and safeguarding the quality of their services to achieve and maintain clinical service excellence ( 21 23 ). Clinical practice guidelines are typically evidence-based and informed by rigorous methodology ( 24 ), and can enhance clinical effectiveness and serve to assess quality assurance, as they are primarily designed to improve processes and outcomes of health interventions ( 25 ).…”
Section: Global Directions For Health Service Delivery Health System ...mentioning
confidence: 99%
“…Aspects of good health governance encompass oversight, policy guidance, collaboration, regulation, accountability and system design and require a human rights approach, technical and political action, and attention to corruption ( 20 ). Clinical governance is defined by healthcare providers' accountability for continuously improving and safeguarding the quality of their services to achieve and maintain clinical service excellence ( 21 23 ). Clinical practice guidelines are typically evidence-based and informed by rigorous methodology ( 24 ), and can enhance clinical effectiveness and serve to assess quality assurance, as they are primarily designed to improve processes and outcomes of health interventions ( 25 ).…”
Section: Global Directions For Health Service Delivery Health System ...mentioning
confidence: 99%
“…The organisation and implementation of Multicap's CBF approach was informed by the principles of the Victorian Government's Multiple and Complex Needs Initiative (MACNI; Victorian Government, 2020) and clinical governance. Clinical governance was originally described in efforts to reform the National Health Service in the United Kingdom (UK)—it is the term used for systems that use organisational structures and culture change to improve patient outcomes (Vassos et al, 2019). Vassos et al (2019, p. 68) describes clinical governance as ‘the implementation of a set of planned and proactive organisational approaches to ensure quality care for service users’.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical governance was originally described in efforts to reform the National Health Service in the United Kingdom (UK)—it is the term used for systems that use organisational structures and culture change to improve patient outcomes (Vassos et al, 2019). Vassos et al (2019, p. 68) describes clinical governance as ‘the implementation of a set of planned and proactive organisational approaches to ensure quality care for service users’. It is suggested that the CBF and its place in a structured PBS approach constitutes a useful model for clinical governance supporting people with challenging behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical governance is defined as “a framework that obliges health service providers to adhere to the principles of clinical service excellence, thereby holding them accountable for maintaining and enhancing the quality of the services they provide.”[ 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%